EFEK ANTIHIPERGLIKEMIA DARI EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus L.) YANG DIINDUKSI SUKROSA - Manurung, Sondang; Barung, Elisabeth; Bodhi, Widhi (UNIVERSITAS SAM RATULANGI, 2012)
This study aims to determine the effects of pericarp extracts of mangosteen antihiperglikemia inwistar strain male mice induced sucrose and compare its effectiveness with glibenclamide. Themethod used is a laboratory experiment using a Completely Randomized Design. Subjects in the formof 15 male white rats tail with weight ranging from 100g-210g are divided into 3 groups of eachgroup as much as 5 tails. The treatment begins with administration of sucrose solution is adjusted tothe weight of each rat. On the second day evening, the test animals fasted for twelve hours, and thethird day in the morning followed by blood glucose level measured sucrose solution, after thirtyminutes of administration of sucrose solution was measured blood glucose level, the first group weregiven distilled water, the second group were given mangosteen rind extract 20%, The third group wasgiven glibenclamide and 0.3030 mg/g weight had made suspension in 1% CMC solution is thenmeasured blood sugar test animals one, two, three, and four hours. Data were analyzed with spssver.17, the real difference between treatments was tested by one way ANOVA. The results ofstatistical analysis gave a significant difference p-value=0.00 (p <0.05) in which the extract cansuppress the KBM 20% increase in KGD in mice and provide similar effectiveness withglibenclamide.Key Word : Garcinia mangostana L., Rattus norvegicus L., Sucrose, CMC